New Directions in Antimatter Chemistry and Physics
DOI: 10.1007/0-306-47613-4_22
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Positron Annihilation on Molecules

Abstract: Two basic mechanisms of positron annihilation in binary collisions with molecules are considered -direct and resonant. The contribution of the former is enhanced, together with the elastic scattering cross section, if the positron has a low-lying virtual level or a weakly bound state with the molecule. For room-temperature positrons it can give Z eff up to 10 3 . The latter mechanism is a two-stage process, whereby the positron is first captured into a vibrationally excited state of the positron-molecule compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
3

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 43 publications
(60 reference statements)
1
41
0
3
Order By: Relevance
“…Other interesting observations are: (i) the annihilation rates for the deuterated and protonated alkanes are very similar if not identical at room temperatures; (ii) singly fluorinated hydrocarbons have even higher annihilation rates whereas further fluorination leads to a decrease of annihilation rate with the perfluorinated molecule having the lowest rate; (iii) there is no strong correlation between Z eff and molecular dipole moment. A theoretical model (Gribakin, 2000(Gribakin, , 2001Iwata et al, 2000) with two regimes was proposed to explain the observed rates. According to the first mechanism, annihilation enhancement can occur due to a weakly bound or a virtual state in the positron-molecule complex.…”
Section: C6 Methyl Iodide Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Other interesting observations are: (i) the annihilation rates for the deuterated and protonated alkanes are very similar if not identical at room temperatures; (ii) singly fluorinated hydrocarbons have even higher annihilation rates whereas further fluorination leads to a decrease of annihilation rate with the perfluorinated molecule having the lowest rate; (iii) there is no strong correlation between Z eff and molecular dipole moment. A theoretical model (Gribakin, 2000(Gribakin, , 2001Iwata et al, 2000) with two regimes was proposed to explain the observed rates. According to the first mechanism, annihilation enhancement can occur due to a weakly bound or a virtual state in the positron-molecule complex.…”
Section: C6 Methyl Iodide Clustersmentioning
confidence: 99%
“…According to recent work on positron annihilation rates (Gribakin, 2000(Gribakin, , 2001, a high density of VFRs, growing exponentially with the number of atoms in the molecule, is required in order to explain the measured annihilation rates. This was confirmed by recent experiments of Barnes et al (2003) which indicate a strong correlation between the spectrum of vibrational modes and the annihilation spectrum for propane and heptane (see Fig.…”
Section: C6 Methyl Iodide Clustersmentioning
confidence: 99%
“…Since the vibrational motion of the molecules is quantized, these transitions can only take place at specific positron energies. These energies correspond to vibrational Feshbach resonances of the positronmolecule complex [21][22][23]. The majority of the resonances observed are associated with individual vibrational modes of the molecule.…”
Section: Introductionmentioning
confidence: 93%
“…The wave function of the weakly bound positron is diffuse and located mostly outside the atom; hence, we describe it using the zero-range-potential model [68] (see also Refs. [23,51,54]). …”
Section: A Calculation Of the Cross Sectionmentioning
confidence: 99%
“…The cross section for this process depends on the incident Ps energy, the initial state nl of Ps, and on the positron-atom binding energy ε b . Reaction (2) leads to rapid positron annihilation; the positron-atom bound state lifetime is [51,52] …”
Section: Introductionmentioning
confidence: 99%